1992
DOI: 10.1002/star.19920440402
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Studies on Starches Isolated from Plantain Cultivars, Plantain Hybrids and Cooking Bananas

Abstract: Starches from mature, unripe fruit pulp of plantain cultivars (Musa supp., AAB group) representing the wide variability in Africa, tetraploid and diploid plantain hybrids and starchy cooking bananas (Musa spp., ABB group) were isolated and characterised. In general, studies revealed very compact irregularly shaped and sized granules, with low amylose content (9.11–17.16%), highly resistant to bacterial α‐amylase attack; Brabender amylograms showed very restricted swelling type patterns with great stability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
32
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 19 publications
21
32
2
1
Order By: Relevance
“…The isolated starches had higher protein and low fat compared to what was reported for banana by Bello‐Pérez et al. (2000b) and for plantain by Rasper (1969) and Eggleston et al. (1992).…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…The isolated starches had higher protein and low fat compared to what was reported for banana by Bello‐Pérez et al. (2000b) and for plantain by Rasper (1969) and Eggleston et al. (1992).…”
Section: Resultssupporting
confidence: 43%
“…(2009); (Mexico). In Nigeria, the authors are aware of only one study (Eggleston et al. 1992) conducted on the functional and physicochemical properties of plantain and cooking banana (fougomou) starches, though there have been studies on the chemical composition of banana and plantain.…”
Section: Introductionmentioning
confidence: 99%
“…That implies good gel stability. This result confirms those of Eggleston et al (1992) that indicated a great stability and a negligible retrogradation on several plantain (Musa spp., AAB group) starches. The gel instability Index of hybrids CRBP 14, CRBP 36 and FHIA 21 (-0.94; -0.82 and -0.…”
Section: Discussionsupporting
confidence: 90%
“…These pores appeared to be irregular closed spheroids in shape and the cell wall thickness was about 2 μm (Figure 7B). The isolated starch appeared to have a smooth surface and was mostly irregular ellipsoid in shape and flaky in nature (Figure 8A and 8B) similar to that of the mango ginger ( Curcuma amada ) and banana starches (Eggleston and others 1992; Policegoudra and Aradhya 2008). It is interesting to note that this flaky starch can pack well during the development of compacted products because of the structural similarity.…”
Section: Resultsmentioning
confidence: 83%